Fisheri Industry Development Strategy From The Perspective Of Maqasid Al-Syari’ah In Belawan - Ryan Syahputra; Muhammad Arif; Muhammad Ikhsan Harahap (Universitas Trunodjoyo Madura, 2025)
The sharp decline in the volume and value of marine fisheries production at the Belawan Ocean Fishing Port (PPS) over the past three years indicates a structural crisis that requires values-based solutions. This study aims to formulate a strategy for developing the marine fisheries industry through a maqasid al-syariah approach as the foundation for equitable and sustainable economic development. The method used is a qualitative descriptive technique with semi-structured interviews with fisheries business actors, followed by a SWOT analysis to identify internal and external factors in the industry. The results indicate weak business capacity due to limited fishing gear, access to capital, and digital literacy, despite the potential for significant resources and government support. The development strategy formulated includes strengthening sharia institutions, technological modernization, Islamic value-based training, and marine environmental preservation, which are aligned with the six dimensions of maqasid al-syariah: protection of religion, life, mind, descendants, property, and the environment. This approach is considered capable of providing a strategy that is not only economically viable, but also ethical, inclusive, and sustainable..Keywords: Belawan Islamic Economym, Fishing Industry, Maqasid al-Shariah